THE EFFECTIVENESS OF SPEED WORD GAMES TO ENHANCE STUDENTS' VOCABULARY ACQUISITION AT SMK DHARMA BHAKTI TOMOHON - Lasut, Gabriella Patricia; Tuerah, Ignatius J. C.; Hampp, Paula (Program Studi Pendidikan Bahasa Inggris, 2024)
This study focused on the use of interactive Speed Word Games, which included two word games there are speed scrabble and speed charades, to enhance students' vocabulary acquisition at SMK Dharma Bhakti Tomohon. The research subjects consisted of 15 students from class X Health. A quantitative research method was used, with a pre- and post-test design involving just one group. This study used a multiple-choice test consisting of twenty-five items as its instrument. The data were analyzed using the mean score formula. 48.8 was the students' pretest score, and 80.8 was their post-test score. According to the study's findings, the mean post-test score increased by 32% over the pre-test score. This proved that the use of Speed Word Games is effective in enhancing students' vocabulary acquisition at SMK Dharma Bhakti Tomohon. Finally, this study suggests that Speed Word Games can be used as an alternative learning method in English classrooms, particularly for vocabulary acquisition.